(untitled) (Journal of Enam Medical College, 2014)
Background: Urinary tract infection (UTI) is a common and frequently encountered serious morbidity that afflicts the tool not only to all segments of human population but also results in increasing antibiotic resistance due to persistence and mismanagement of the ailment. The present study aimed to ascertain the current situation of antimicrobial resistance of urinary tract infection. Objectives: To find out pyuria by direct microscopy, isolation and identification of the organisms by culture and to know the susceptibility pattern of organisms causing urinary tract infection. Materials and Methods: A total of 180 midstream urine samples were subjected to aerobic bacteriologic culture in the department of Microbiology, Coxs Bazar Medical College and 250-bedded Sadar Hospital, Coxs Bazar during the period of March to October 2012. Specimens were collected from hospitalized and outdoor patients of different age and sex groups. All specimens were examined by routine microscopy to find out significant pyuria (>5 pus cells/HPF). Strict aseptic precautions were taken all through the culture system. Results: Out of 180 specimens, 101 (56.11%) culture yielded significant growth of single organism and 79 (43.89%) yielded no growth. The isolated organisms were E. coli 74.26%, Klebsiella species 12.87%, Enterococci 4.95%, Staphylococcus saprophyticus 3.96%, Pseudomonas species 1.98% and Proteus species 1.98%. The highest sensitivity was shown by imipenem (100%) followed by ceftriaxone (65%), azithromycin (65%), ciprofloxacin (60%) and less sensitive to amoxycillin, cotrimoxazole, cephradine and nalidixic acid ranging 1530%. Conclusion: The findings of the present study recommends that UTI should be treated by selective antibiotics obtained from culture and sensitivity test to minimize increasing trend of drug resistance. DOI: http://dx.doi.org/10.3329/jemc.v4i1.18064 J Enam Med Col 2014; 4(1): 21-25